(untitled) (European Journal of Pure and Applied Mathematics, 2010)
The Royal Statistical Society, Japan Statistical Society, The University of Melbourne, University of Canterbury and European Journal of Pure and Applied Mathematics publish their institutional tributes and messages in this honorary volume. Professors Halbert White, Harald Uhlig, Robin Harrison, Les Oxley, Michelle Blackmore and Roselyne Joyeux send their personal tributes and messages to Sir Granger. Some authors of this special issue include their tributes in their papers.